Reducing student teachers' foreign language pronunciation anxiety through psycho-social training. (April 2017) - Kralova, Zdena; Skorvagova, Eva; Tirpakova, Anna; Markechova, Dagmar
Abstract: Foreign language anxiety (FLA) is one of the most examined affective variables in the field of foreign language (FL) learning and researchers have verified FLA reducing strategies of various kinds. In this study, psycho-social training as an FLA reducing strategy was applied to a group of TEFL students (experimental group) combined with intensive English pronunciation training (experimental and control groups). Psycho-social training is a non-therapeutic intervention program of active social learning that should help individuals cope with stressful situations. A self-reported Foreign Language Pronunciation Anxiety (FLPA) questionnaire was used to examine the students' English pronunciation anxiety before and after the training and the students' English pronunciation was evaluated before and after the training. Based on the results of the statistical analysis it can be stated that the levels of pronunciation anxiety and pronunciation quality were similar in both groups before the training. After the training, anxiety was significantly lower and pronunciation quality was significantly higher in the experimental group.